Faktor-Faktor yang mempengaruhi Kinerja Kepala dan Kinerja Aparatur SOPD dan Kepuasan Pelayanan Publik - Yusuf Tawalo (Kontigensi : Jurnal Ilmiah Manajemen, 2015)
This research employed a sampling technique with a proportional stratified random sampling technique. The analysis method used was descriptive and verivicative methods, beginning with questionnaire spread, data collection, presentation, and analysis, hypothesis test, discussion and finally the making of conclusion and suggestion. The findings of research showed the total of direct and indirect influences of the variables: Education and Training, Managerial Capacity, Occupational Sphere, Entrepreneurship Spirit, Technology Mastering and Informasi on the performance of SOPD head was 73.23 per cent. Meanwhile, the influence of SOPD head’s performance on the employees’ performance was 80.40 per cent. And the extent of the influence of employees’ performance on the satisfaction of public service was 88.30 per cent. The conclusion of the research findings was that the performance of SOPD head was not optimal, so that the performance of the employees was equally not optimal, hence it could not convey satisfaction of service to public maximally.